Application of the Finite Element Method to the Investigation of Composite Materials. Approaches, Methods, Computer Programms - E.N. Kniazeva (National Academy of Sciences of Belarus, State Scientific Institution “The Joint Institute of Mechanical Engineering", 2013)
Main approaches to application of finite element method to the investigation of composite materials are reviewed and analyzed, including theoretical suggestions, direct calculation of representative volumes of composites by means of universal computer packages, using of specialized programs. Advantages, disadvantages, limitations and perspectives of using of different approaches in the investigation of mechanical properties of composite materials are shown. Experience of application of finite element modeling to the improvement of properties of composites so as to the explanation of micro-level processes is also reviewed.